2007
DOI: 10.1292/jvms.69.657
|View full text |Cite
|
Sign up to set email alerts
|

Meningoventriculitis Caused by Streptococcus pluranimalium in a Neonatal Calf of Premature Birth

Abstract: ABSTRACT. Pathological and bacteriological examinations were carried out on a neonatal calf that had developed nervous symptoms such as opisthotonus and blindness since it was born one month prior to full term. The principal lesions were characterized by fibrinopurulent inflammation of the meninges, choroid plexuses, and ventricular walls with limited extension to the subependymal parenchyma in the spinal cord. Purulent inflammation was also found in several visceral organs and tissues. Streptococcus pluranima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…S. pluranimalium is classified under unusual streptococcus species which includes streptococci which are not beta hemolytic and not part of the viridans group [4]. The organism has been associated with diseases in animals (primarily in bovine and avian species) causing septicaemia and valvular endocarditis in adult broiler parents [5], subclinical mastitis in cows [1] and purulent meningoventriculitis in a calf [6].…”
Section: Discussionmentioning
confidence: 99%
“…S. pluranimalium is classified under unusual streptococcus species which includes streptococci which are not beta hemolytic and not part of the viridans group [4]. The organism has been associated with diseases in animals (primarily in bovine and avian species) causing septicaemia and valvular endocarditis in adult broiler parents [5], subclinical mastitis in cows [1] and purulent meningoventriculitis in a calf [6].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pluranimalium is one of the newer strains of Streptococcus, first identified by Devriese et al in 1999; the authors coined the term ‘ pluranimalium ’ meaning ‘from many animals’ ( pluris many, animalium from animals) due to the fact that this particular species was isolated on several different animal hosts. 10 Over the years since the strain was first described, it has been identified as a causative pathogen in septicemia and valvular endocarditis in broiler chickens, 11 subclinical mastitis in dairy cows 10 and purulent meningoventriculitis in a calf, 12 it has also been associated with many bovine reproductive diseases such as abortion, stillbirth, vulvitis, vaginitis and metritis. 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…S. pluranimalium was isolated from panda 3 when it was Alvei profluvium. Seimiya et al (2007) has reported S. pluranimalium was isolated from the brain and cerebrospinal fluid of a neonatal calf (Seimiya et al, 2007), so the isolated S. pluranimalium may cause Giant panda Alvei profluvium. 2 S. alactolyticus was isolated from nasal cavity and anus of panda4 who is a wild Giant panda.…”
Section: Discussionmentioning
confidence: 99%